Factors Associated with Health Seeking Behaviour of Pneumonia Children Under Five in Lubuk Begalung Health Center 2024 - Silvia Amanda Lodi; Ade Suzana Eka Putri; Yeffi Masnarivan; Dien Gusta Anggraini Nursal (JURNAL KESMAS DAN GIZI (JKG), 2026)
Pneumonia remains a major contributor to mortality due to infectious diseases among children under five worldwide. Inappropriate health-seeking behavior when a child develops pneumonia may potentially result in delays in obtaining adequate medical care, thereby increasing the risk of complications and mortality. This study aimed to analyze the factors associated with health-seeking behavior for pneumonia among children under five in the working area of Lubuk Begalung Community Health Center. This study employed a cross-sectional design and was conducted at the Lubuk Begalung Community Health Center from February to June 2024. The study involved 87 mothers of children under five diagnosed with pneumonia who were selected using a simple random sampling technique. The findings revealed that 62.1% of respondents exhibited poor health-seeking behavior. There were significant associations between health-seeking behavior for pneumonia among children under five and maternal age (p = 0.004), maternal knowledge (p < 0.0001), and perceived severity of illness (p = 0.014). Family income (p = 0.017; PR = 16.406; 95% CI: 1.642–163.900) was the most dominant factor associated with treatment-seeking behavior for pneumonia among under-five children at Lubuk Begalung Primary Health Center, Padang. It is recommended that the Padang City Health Office and Lubuk Begalung Primary Health Center implement educational interventions on the signs, symptoms, and danger signs of pneumonia in under-five children and the importance of timely healthcare-seeking at health facilities, in order to reduce the risk of mortality and disease severity among children under five.